Answer:
(5, 3 ) and (-
, - 10 )
Step-by-step explanation:
Given the 2 equations
2x - y = 7 → (1)
xy = 15 → (2)
Rearrange (1) expressing y in terms of x , that is
y = 2x - 7 → (3)
Substitute y = 2x - 7 into (2)
x(2x - 7) = 15
2x² - 7x = 15 ( subtract 15 from both sides )
2x² - 7x - 15 = 0 ← in standard form
(x - 5)(2x + 3) = 0 ← in factored form
Equate each factor to zero and solve for x
x - 5 = 0 ⇒ x = 5
2x + 3 = 0 ⇒ 2x = - 3 ⇒ x = - ![\frac{3}{2}](https://tex.z-dn.net/?f=%5Cfrac%7B3%7D%7B2%7D)
Substitute these values into (3) for corresponding values of y
x = 5 : y = 2(5) - 7 = 10 - 7 = 3 ⇒ (5, 3 )
x = -
: y = 2(-
) - 7 = - 3 - 7 = - 10 ⇒ (-
, - 10 )
Answer:
122
Step-by-step explanation:
32+32+29+29=122
Let
![x](https://tex.z-dn.net/?f=x)
be the amount of time it takes to perform an arm routine and
![y](https://tex.z-dn.net/?f=y)
be the amount of time it takes to perform an abdominal routine. We see:
![4x+y=70](https://tex.z-dn.net/?f=4x%2By%3D70)
![4x+2y=100](https://tex.z-dn.net/?f=4x%2B2y%3D100)
Subtracting the second equation from the first gives
![y=30](https://tex.z-dn.net/?f=y%3D30)
. Substituting gives
![4x+30=70](https://tex.z-dn.net/?f=4x%2B30%3D70)
, so
![4x=40](https://tex.z-dn.net/?f=4x%3D40)
and
![x=10](https://tex.z-dn.net/?f=x%3D10)
.
Thus, an arm routine takes ten minutes and an abdominal routine takes thirty minutes.
5x^4
Step-by-step explanation:
simply we take 5x^4 bec. it can be divided by 40 and 135
Answer:
ab=bc because b devide ac in two equal sizes
ac=ab+bc
ac=2×ab
ac =2×bc
lets substitute ac and bc there we are given
x+3=2(3x-1)
x+3=6x-2
-5x/-5=-5/-5
x=1
ab=3(1)-1
ab=2